A friction nanogenerator with a multi-layer friction layer and its preparation and application

By designing a friction nanogenerator with a multi-layer structure friction layer, the problem of difficulty in achieving electrochemical cathode protection in the ocean environment is solved, and efficient electrical energy conversion and electrochemical cathode protection is achieved, which is suitable for power-deficient areas.

CN115498916BActive Publication Date: 2024-12-13INST OF OCEANOLOGY - CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202211188698.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-28
Publication Date
2024-12-13
Estimated Expiration
2042-09-28

AI Technical Summary

Technical Problem

Traditional applied current cathode protection is difficult to achieve in ocean environments and complex environments where electricity is scarce, and tribonanogenic technology is insufficient for electrochemical cathode protection in these areas.

Method used

A friction nanogenerator with a multi-layer structural friction layer was designed, including a top electrode and a bottom electrode. The top electrode consists of a conductive film, and the bottom electrode consists of a Mxene/melamine foam layer, a silicone rubber layer and a TiO2 nanotube array layer. Adhesive to the lower substrate by self-adsorption and pasting with foam buffer layers, an efficient friction nanogenerator is formed to convert environmental mechanical energy into electrical energy and is used in electrochemical cathode protection.

Benefits of technology

It improves the charge density and electrical output performance of friction nanogenerators, solves the problem of electrochemical cathode protection in remote environments, and provides an effective corrosion protection solution without the need for external power systems, suitable for power-deficient areas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115498916B_ABST
    Figure CN115498916B_ABST
Patent Text Reader

Abstract

The present invention relates to a friction nanogenerator with a multilayer friction layer, and its preparation and application. The generator comprises a substrate, a positive friction layer, a negative friction layer, an electrode, a wire and a connecting spring. The negative friction layer is composed of a silicone rubber-wrapped Mxene / melamine foam layer and a TiO2 nanotube array self-adsorbed, i.e., a Mxene / melamine foam layer / silicone rubber / TiO2 layer. The Mxene / melamine foam layer / silicone rubber / TiO2 layer can effectively improve the charge density of the friction nanogenerator by electron transfer and capture, and further improve the electrical output performance of the friction nanogenerator. The friction nanogenerator can convert mechanical energy in the environment into electrical energy, and can be widely used in the field of electrochemical cathode protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of generators and their preparation and application, and in particular relates to a friction nanogenerator with a multi-layer friction layer and its preparation and application. Background Art

[0002] With the development of the times, human beings' utilization and demand for energy are increasing, and environmental damage caused by energy problems is becoming increasingly prominent, and global climate crises are frequent. Traditional fossil energy is the main energy source for human development at present, but its quantity is limited, which will seriously limit human development in the near future and even cause devastating disasters. Therefore, resource shortages and energy crises will be important difficulties that humans need to solve in the future. With the proposal of the "dual carbon" goal, vigorously developing new energy is the best choice to solve energy problems and achieve low carbonization. In recent years, scientists have made a lot of contributions to the development of new energy. Among them, the friction nano-power generation technology proposed by Wang Zhonglin's team in 2012 can convert low-frequency and disordered low-grade mechanical energy in the environment into electrical energy, and can instantly drive functional electronic devices; in human daily life, many energies, such as energy generated by human movement, rolling waves, and air flow, can be collected by friction nano-generators; therefore. The development of friction nano-generators is of great significance in resolving energy crises, benefiting mankind and improving the quality of life. In addition, energy and resource issues in metal corrosion protection are also particularly prominent. Corrosion is a common problem faced by the whole world, which will cause significant property losses and seriously threaten human life and safety. The disasters caused by metal corrosion failure are countless. Electrochemical cathodic protection is an important means of corrosion protection, which mainly includes impressed current cathodic protection and sacrificial anode cathodic protection. Among them, impressed current cathodic protection requires the support of an external power system. Traditional impressed current cathodic protection is implemented under the existing power system and is generally suitable for areas with developed power systems. It is still difficult to achieve electrochemical cathodic protection in offshore environments with scarce electricity and remote areas with complex environments. The advantages of friction nano-generation technology in collecting and converting any mechanical properties in the environment into electrical energy can effectively solve the problem that electrochemical cathodic protection cannot be achieved in remote environments. Therefore, it is of great significance to develop and utilize friction nano-generators and improve the output performance of friction nano-generators to achieve electrochemical cathodic protection. Summary of the invention

[0003] The present invention aims to provide a friction nanogenerator with a multi-layer friction layer and its preparation and application.

[0004] To achieve the above purpose, the present invention adopts the following technical solution:

[0005] A friction nanogenerator with a multi-layer friction layer, the friction nanogenerator includes an electrode, a wire and a connecting base spring,

[0006] The electrode is divided into a top electrode and a bottom electrode, wherein the top electrode is composed of a positive friction layer and an upper substrate; the bottom electrode is composed of a negative friction layer with a multi-layer structure and a lower substrate;

[0007] Wires, which are respectively led out from the top electrode and the bottom electrode;

[0008] At least four connecting substrate springs are used to connect the upper substrate and the lower substrate.

[0009] The positive friction layer is composed of a conductive film and is adhered to the upper substrate via a foam buffer layer;

[0010] The negative friction layer with a multi-layer structure consists of a Mxene / melamine foam layer, a silicone rubber layer and a TiO2 nanotube array layer; the silicone rubber wraps the Mxene / melamine foam, adheres to the TiO2 nanotube array by self-adsorption, and is adhered to the lower substrate through the foam buffer layer.

[0011] The self-adsorption adhesion normal stress between the Mxene / melamine foam / silicone rubber layer and the TiO2 nanotube array is greater than 10N, and the shear stress is greater than 2N. The resistance of the Mxene / melamine foam is less than 200Ω. The dielectric constant of the Mxene / melamine foam / silicone rubber / TiO2 layer is greater than 5.0. The working mode of the friction nanogenerator is contact separation.

[0012] Preparation of the negative friction layer with a multi-layer structure:

[0013] (a) hot pressing the melamine foam, using a hot pressing plate to hot press at 230-240° C. to obtain a hot pressed melamine foam;

[0014] (b) drop-coating the Mxene aqueous solution onto the hot-pressed melamine foam to obtain a Mxene / melamine foam layer;

[0015] (c) casting silicone rubber, mixing silicone rubber component A and component B in a volume ratio of 1:1, and casting the Mxene / melamine foam layer to obtain a Mxene / melamine foam / silicone rubber layer;

[0016] (d) Preparation of TiO2 nanotube arrays on Ti foil;

[0017] (e) Self-adhere the Mxene / melamine foam / silicone rubber layer onto the TiO2 nanotube array to obtain a Mxene / melamine foam / silicone rubber layer / TiO2 layer.

[0018] The silicone rubber component A is a prepolymer (for example, Ecoflex00-10 A; Ecoflex00-30 A); and the component B is an adhesive (for example, Ecoflex00-10 B; Ecoflex00-30 B).

[0019] The positive friction layer is a conductive film, such as Al foil, Cu foil, carbon cloth, etc.;

[0020] The foam buffer layer is an elastic double-sided tape;

[0021] The substrate is made of an acrylic plate or any other material with a certain mechanical strength.

[0022] A method for preparing a friction nanogenerator with a multi-layer friction layer:

[0023] The positive friction layer is adhered to the upper substrate through the foam buffer layer as a top electrode;

[0024] The negative friction layer with multilayer structure adheres to the TiO2 nanotube array as the bottom electrode by self-adsorption;

[0025] Lead wires are led out from the top electrode and the bottom electrode respectively, and at least four connecting substrate springs are connected to the upper substrate and the lower substrate.

[0026] Preparation of the negative friction layer with a multi-layer structure:

[0027] (a) hot pressing the melamine foam, using a hot pressing plate to hot press at 230-240° C. to obtain a hot pressed melamine foam;

[0028] (b) drop-coating the Mxene aqueous solution onto the hot-pressed melamine foam to obtain a Mxene / melamine foam layer;

[0029] (c) casting silicone rubber, mixing silicone rubber component A and component B in a volume ratio of 1:1, and casting the Mxene / melamine foam layer to obtain a Mxene / melamine foam / silicone rubber layer;

[0030] (d) Preparation of TiO2 nanotube arrays on Ti foil;

[0031] (e) Self-adhere the Mxene / melamine foam / silicone rubber layer onto the TiO2 nanotube array to obtain a Mxene / melamine foam / silicone rubber layer / TiO2 layer.

[0032] The concentration of the Mxene aqueous solution is 5%wt-10%wt.

[0033] After casting the silicone rubber, the Mxene / melamine foam layer needs to be cured at room temperature for more than 4 hours to obtain the Mxene / melamine foam / silicone rubber layer.

[0034] The silicone rubber component A is a prepolymer; and component B is an adhesive.

[0035] An application of a friction nanogenerator with a multi-layer friction layer, and an application of the friction nanogenerator in electrochemical cathode protection.

[0036] The advantages of the present invention are:

[0037] The friction nanogenerator of the present invention comprises a substrate, a positive friction layer, a negative friction layer, an electrode, a wire and a connecting spring. The substrate can be composed of an acrylic plate or any other material with a certain mechanical strength, which is easy to obtain. The positive friction layer is composed of a conductive material that is easy to lose electrons, which is easy to prepare and low in cost. The negative friction layer is composed of a silicone rubber wrapped Mxene / melamine foam layer and a TiO2 nanotube array self-adsorbed to form a multilayer structure, namely Mxene / melamine foam layer / silicone rubber / TiO2 layer, and the Mxene / melamine foam layer / silicone rubber / TiO2 layer can effectively improve the charge density of the friction nanogenerator through electron transfer and capture, and further improve the electrical output performance of the friction nanogenerator. The present invention uses melamine foam to evenly disperse Mxene and successfully solves the problem of its difficulty in dispersing in silicone rubber. The method is simple and easy. From the perspective of mechanism, the present invention utilizes the conductivity and strong electronegativity of Mxene to not only transfer the surface charge of the negative friction layer to a deeper depth, but also effectively capture more charges. In addition, the high dielectric constant of the TiO2 layer of the present invention further polarizes and strengthens the electrical properties of the negative friction layer. In general, the synergistic effect of the electrical conductivity, strong electronegativity and high dielectric properties of Mxene and TiO2 in the Mxene / melamine foam layer / silicone rubber / TiO2 layer of the present invention jointly improves the electrical properties of the negative friction layer, thereby further effectively improving the output of the friction nanogenerator. In addition, the present invention uses the self-adhesion effect between silicone rubber and TiO2 to fix the two together, which not only improves the stability of the friction layer, but also avoids the influence of traditional adhesive glue on the output of the friction layer. The friction nanogenerator can convert mechanical energy in the environment into electrical energy and can be widely used in the field of electrochemical cathodic protection. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 Schematic diagram of the friction nanogenerator in the present invention;

[0039] Figure 2 A schematic diagram of the working principle of the friction nanogenerator in the present invention;

[0040] Figure 3This is a graph showing the test results of the conductivity of Mxene / melamine foam provided in Example 2 of the present invention;

[0041] Figure 4 This is a graph showing the adsorption test results between Mxene / melamine foam / Ecoflex and TiO2 nanotube array provided in Example 2 of the present invention;

[0042] Figure 5 This is a test curve of the amount of charge transferred by the triboelectric nanogenerator provided in Example 2 of the present invention;

[0043] Figure 6 This is a short-circuit current test curve of the triboelectric nanogenerator provided in Example 2 of the present invention;

[0044] Figure 7 This is the open circuit voltage test curve of the triboelectric nanogenerator provided in Example 2 of the present invention;

[0045] Figure 8 The triboelectric nanogenerator provided in Example 2 of the present invention forms a cathodic protection open circuit potential curve for a Q235 carbon steel electrode;

[0046] Fig. 9 This is a test diagram of the resistance of Mxene / melamine foam contained in the negative friction layer of the triboelectric nanogenerator provided in Example 3 of the present invention;

[0047] Fig.10 This is a short-circuit current test curve of the triboelectric nanogenerator provided in Example 3 of the present invention;

[0048] Fig.11 This is the open circuit voltage test curve of the triboelectric nanogenerator provided in Example 3 of the present invention;

[0049] Fig.12 The triboelectric nanogenerator provided in Example 3 of the present invention forms a cathodic protection open circuit potential curve for a Q235 carbon steel electrode. DETAILED DESCRIPTION

[0050] The present invention will be further described in detail below in conjunction with the accompanying drawings and the following embodiments, but the contents of the present invention are not limited thereto.

[0051] Example 1

[0052] A triboelectric nanogenerator with a multilayer friction layer, such as Figure 1 As shown, it includes a substrate, a positive friction layer, a negative friction layer, electrodes (top electrode and bottom electrode), wires, and a spring connecting the substrate.

[0053] Wires are led out from the top electrode and the bottom electrode to derive electrical signals, and the substrates of the two electrodes are connected by at least one connecting substrate spring.

[0054] The substrate comprises an upper substrate and a lower substrate; the positive friction layer is composed of a conductive film and is adhered to the substrate through a foam buffer layer; the negative friction layer having a multi-layer structure is composed of a Mxene / melamine foam layer, a silicone rubber layer and a TiO2 nanotube array layer; the silicone rubber wraps the Mxene / melamine foam, adheres to the TiO2 nanotube array by self-adsorption, and is adhered to the lower substrate through the foam buffer layer;

[0055] The working principle of the friction nanogenerator of the present invention is as follows Figure 2 As shown in the figure, under the action of external force, the positive friction layer and the negative friction layer contact each other, and carry positive and negative charges respectively due to frictional electrification. When the external force is removed, the positive friction layer and the negative friction layer separate from each other. Due to electrostatic induction and potential difference, electrons move between external circuits, thereby outputting current. This reciprocating motion forms alternating current that is output to the outside.

[0056] Example 2

[0057] The preparation method of the friction nanogenerator having a multi-layer friction layer is specifically as follows:

[0058] Preparation of the substrate: Use a laser machine to obtain two acrylic plates with a specification of 5×5×0.3cm, and use a bench drill to process grooves with a depth of 0.1cm and a diameter of 0.5cm at the four corners of the acrylic plate to fix the spring connected to the substrate. And adhere 2.5×2.5×0.2cm double-sided foam glue to the grooved surface as a buffer layer for the positive and negative friction layers.

[0059] Cut two pieces of aluminum foil with a thickness of 2.5×2.5×0.01 cm, one piece as the conductive film of the positive friction material; the other piece as the conductive film on the back of the negative friction material.

[0060] Cut two 15cm long wires and set aside.

[0061] A conductive film used as a positive friction material is adhered to the buffer layer, and the above-mentioned 15 cm long wire is connected to the conductive film and led out for measuring the electrical output.

[0062] Preparation of negative friction layer of friction nanogenerator with multilayer friction layer:

[0063] First, the original melamine foam with a specification of 2.5×2.5×0.2 cm was cut and hot-pressed at 230° C. using a hot pressing plate to obtain a hot-pressed melamine foam; then, a 5% wt Mxene aqueous solution was drop-coated on the hot-pressed melamine foam to obtain a Mxene / melamine foam layer; then, silicone rubber component A and component B were mixed in a formula of 1:1 by volume, cast onto the Mxene / melamine foam layer, and allowed to stand at room temperature for 4 hours to obtain a Mxene / melamine foam / Ecoflex layer;

[0064] Among them, the silicone rubber component A is the prepolymer Ecoflex00-10 A, and the component B is the adhesive Ecoflex00-10 B.

[0065] Secondly, TiO2 nanotube arrays were prepared by cutting commercially available titanium plates (purity of 99.9%) into samples of 2.5×2.5×0.03 cm. The samples were ultrasonically cleaned several times with pure water and acetone for 20 minutes each time to remove inorganic or organic impurities on the surface of the samples, and then dried at room temperature for later use.

[0066] First, dissolve 0.9g of ammonium fluoride (NH4F) in 5mL of pure water, then add 12mL of hydrogen peroxide (H2O2) and 12mL of nitric acid (65% HNO3) in turn and stir evenly with a magnetic stirrer to obtain a polishing solution. Immerse the titanium plate sample in the polishing solution and chemically polish until the surface of the sample is uniform, smooth and free of impurities. After taking it out, ultrasonically clean it twice with pure water and anhydrous ethanol alternately for 10 minutes each time to obtain a clean titanium plate sample. Finally, store it in anhydrous ethanol for later use.

[0067] A TiO2 nanotube array was prepared on the surface of a titanium plate sample by dissolving 0.44 g NH4F in 8 mL pure water, then adding 80 mL ethylene glycol, and stirring the mixture evenly with a magnetic stirrer to obtain an electrolyte for preparing the TiO2 nanotube array.

[0068] 80 mL of the above electrolyte was placed in a 200 mL beaker, the clean titanium plate sample was connected to the positive electrode of the DC power supply, and the platinum foil (2.0×2.0 cm) was connected to the negative electrode of the DC power supply to build a two-electrode system. The voltage was set to 60 V and the reaction time was 1 h. After the reaction was completed, the sample was rinsed alternately with pure water and anhydrous ethanol for several times. After drying at room temperature, the sample was placed in a muffle furnace, the heating rate was set to 5 ° C / min, and calcined at 450 ° C for 120 minutes. After natural cooling, the TiO2 nanotube array was obtained.

[0069] Finally, the Mxene / melamine foam / Ecoflex layer obtained above is adhered to the TiO2 nanotube array by self-adsorption to obtain the negative friction layer of the friction nanogenerator.

[0070] The negative friction layer of the friction nanogenerator with the multi-layer friction layer is attached with the conductive film on the back and adhered to the buffer layer of the lower substrate; and the 15 cm long wire is connected to the conductive film and led out to measure the electrical output.

[0071] The conductivity of the Mxene / melamine foam obtained in Example 2 was measured with a multimeter. During the measurement, the multimeter probe was inserted into any two points on the surface of the Mxene / melamine foam to measure and record the resistance.

[0072] The adsorption force between Mxene / melamine foam / Ecoflex and TiO2 nanotube array in Example 2 was tested with the aid of a weight. During the test, one end of Mxene / melamine foam / Ecoflex and TiO2 nanotube array was fixed to the bracket hook, and a weight of a certain mass was hung on the other end. The adsorption force between Mxene / melamine foam / Ecoflex and TiO2 nanotube array was obtained by conversion using the formula F=mg.

[0073] The multilayer friction layer prepared in Example 2 and the friction nanogenerator assembled according to Example 1 were tested for electrical output performance, including transfer charge, short-circuit current and open-circuit voltage tests. All of them were obtained by Keithley electrometer 6514 and collected and analyzed with the help of a data acquisition card. Among them, the output voltage test was measured under a load of 100MΩ. During the test, the excitation was achieved with the help of a signal generator and an exciter control.

[0074] The conductivity of the Mxene / melamine foam obtained in Example 2 was measured by a multimeter. The results are as follows: Figure 3 The results show that the resistance of Mxene / melamine foam is 104.5Ω, which indicates that it has good conductivity and is conducive to the transfer of electrons in the conductive layer.

[0075] The adsorption force between the Mxene / melamine foam / Ecoflex obtained in Example 2 and the TiO2 nanotube array was tested, and the results are as follows: Figure 4 The results show that the normal stress between Mxene / melamine foam / Ecoflex and TiO2 nanotube array is 10N and the shear stress is 2N, which indicates that the adhesion between the two is strong, which is beneficial to the stability of the friction layer.

[0076] The multilayer friction layer prepared in Example 2 and the friction nanogenerator assembled according to Example 1 were subjected to an external force at a frequency of 5 Hz, so that the positive friction layer and the negative friction layer were in contact and separated, and the amount of charge transferred was 101.2 μC. Figure 5 .

[0077] The multilayer friction layer prepared in Example 2 and the friction nanogenerator assembled according to Example 1 were subjected to an external force at a frequency of 5 Hz, so that the positive friction layer and the negative friction layer were in contact and separated, and the short-circuit current was 21 μA. Figure 6 .

[0078] The multilayer friction layer prepared in Example 2 and the friction nanogenerator assembled according to Example 1 were subjected to an external force at a frequency of 5 Hz, so that the positive friction layer and the negative friction layer were in contact and separated. When an external 100 MΩ resistor was connected, the open circuit voltage was 620 V. Figure 7 .

[0079] The multilayer friction layer prepared in Example 2 and the friction nanogenerator assembled according to the description of Example 1 were connected to a three-electrode system to construct an electrochemical cathodic protection system to test the corrosion protection of Q235 carbon steel: the working electrode in the three-electrode system is Q235 carbon steel, the reference electrode is Ag / AgCl electrode, and the counter electrode is Pt. The electrolytic cell solution is simulated by 3.5% NaCl. After the output electrical signal of the friction nanogenerator is rectified by a full-bridge, the positive current is connected to the three-electrode system Pt, and the negative current is connected to the working electrode Q235 carbon steel. Subsequently, the workstation was used to test the cathodic protection effect of Q235 carbon steel formed by the friction nanogenerator driven by an external force at a frequency of 5 Hz. Figure 8 The results show that the triboelectric nanogenerator can reduce the surface potential of Q235 carbon steel to -1.1 V, indicating that it can form good cathodic protection for Q235 carbon steel.

[0080] Example 3

[0081] The preparation method of the friction nanogenerator having a multi-layer friction layer is specifically as follows:

[0082] Preparation of the substrate: Use a laser machine to obtain two acrylic plates with a specification of 10×10×0.3cm, and use a bench drill to process grooves with a depth of 0.1cm and a diameter of 0.5cm at the four corners of the acrylic plate to fix the spring connected to the substrate. And adhere 5×5×0.2cm double-sided foam glue to the grooved surface as a buffer layer for the positive and negative friction layers.

[0083] Cut two pieces of aluminum foil with a thickness of 5×5×0.01 cm, one piece as the conductive film of the positive friction material; the other piece as the conductive film on the back of the negative friction material.

[0084] Cut two 20cm long wires and set aside.

[0085] A conductive film used as a positive friction material is adhered to the buffer layer, and the above-mentioned 20 cm long wire is connected to the conductive film and led out for measuring the electrical output.

[0086] Preparation of negative friction layer of friction nanogenerator with multilayer friction layer:

[0087] First, the original melamine foam with a specification of 5×5×0.2 cm was cut and hot-pressed at 240°C using a hot pressing plate to obtain the hot-pressed melamine foam; then, a 10%wt Mxene aqueous solution was drop-coated on the hot-pressed melamine foam to obtain the Mxene / melamine foam layer; then, the silicone rubber component A and component B were mixed in a formula of 1:1 by volume, cast on the Mxene / melamine foam layer, and allowed to stand at room temperature for 4 hours to obtain the Mxene / melamine foam / Ecoflex layer;

[0088] Among them, the silicone rubber component A is the prepolymer Ecoflex00-30A, and the component B is the adhesive Ecoflex00-30B.

[0089] Secondly, TiO2 nanotube arrays were prepared by cutting commercially available titanium plates (purity of 99.9%) into samples of 5×5×0.03 cm, and ultrasonically cleaning them repeatedly with pure water and acetone for 20 minutes each time to remove inorganic or organic impurities on the surface of the samples, and then drying them at room temperature for later use.

[0090] First, dissolve 0.9g of ammonium fluoride (NH4F) in 5mL of pure water, then add 12mL of hydrogen peroxide (H2O2) and 12mL of nitric acid (65% HNO3) in turn and stir evenly with a magnetic stirrer to obtain a polishing solution. Immerse the titanium plate sample in the polishing solution and chemically polish until the surface of the sample is uniform, smooth and free of impurities. After taking it out, ultrasonically clean it twice with pure water and anhydrous ethanol alternately for 10 minutes each time to obtain a clean titanium plate sample. Finally, store it in anhydrous ethanol for later use.

[0091] A TiO2 nanotube array was prepared on the surface of a titanium plate sample by dissolving 0.44 g NH4F in 8 mL pure water, then adding 80 mL ethylene glycol, and stirring the mixture evenly with a magnetic stirrer to obtain an electrolyte for preparing the TiO2 nanotube array.

[0092] 80 mL of the above electrolyte was placed in a 200 mL beaker, the clean titanium plate sample was connected to the positive electrode of the DC power supply, and the platinum foil (2.0×2.0 cm) was connected to the negative electrode of the DC power supply to build a two-electrode system. The voltage was set to 60 V and the reaction time was 1 h. After the reaction was completed, the sample was rinsed alternately with pure water and anhydrous ethanol for several times. After drying at room temperature, the sample was placed in a muffle furnace, the heating rate was set to 5 ° C / min, and calcined at 450 ° C for 120 minutes. After natural cooling, the TiO2 nanotube array was obtained.

[0093] Finally, the Mxene / melamine foam / Ecoflex layer obtained above is adhered to the TiO2 nanotube array by self-adsorption to obtain the negative friction layer of the friction nanogenerator.

[0094] The negative friction layer of the friction nanogenerator with the multi-layer friction layer is attached with the conductive film on the back and adhered to the buffer layer of the lower substrate; and the 15 cm long wire is connected to the conductive film and led out to measure the electrical output.

[0095] The conductivity of the Mxene / melamine foam obtained in Example 3 was measured by a multimeter. The results are as follows: Fig. 9 The results show that the resistance of Mxene / melamine foam is 110.9Ω, which indicates that it has good conductivity and is conducive to the transfer of electrons in the conductive layer.

[0096] The multilayer friction layer prepared in Example 3 and the friction nanogenerator assembled according to Example 1 were subjected to an external force at a frequency of 5 Hz, so that the positive friction layer and the negative friction layer were in contact and separated, and the short-circuit current was 43 μA. Fig.10 .

[0097] The multilayer friction layer prepared in Example 3 and the friction nanogenerator assembled according to Example 1 were subjected to an external force at a frequency of 5 Hz, so that the positive friction layer and the negative friction layer were in contact and separated. When an external 100 MΩ resistor was connected, the open circuit voltage was 1461 V. Fig.11 .

[0098] The multilayer friction layer prepared in Example 3 and the friction nanogenerator assembled according to the description of Example 1 were connected to a three-electrode system to construct an electrochemical cathodic protection system to test the corrosion protection of Q235 carbon steel. In the three-electrode system, the working electrode is Q235 carbon steel, the reference electrode is Ag / AgCl electrode, and the counter electrode is Pt. The electrolytic cell solution is simulated by 3.5% NaCl. After the output electrical signal of the friction nanogenerator is rectified by a full-bridge, the positive current is connected to the three-electrode system Pt, and the negative current is connected to the working electrode Q235 carbon steel. Subsequently, the workstation was used to test the cathodic protection effect of Q235 carbon steel formed by driving the friction nanogenerator under an external force with a frequency of 1-10Hz. Fig.12 The results show that the triboelectric nanogenerator can reduce the surface potential of Q235 carbon steel to -1.14 V, indicating that it can provide good cathodic protection for Q235 carbon steel.

[0099] Other preparation methods not exemplified can be easily implemented under the guidance of the above two preparation methods and will not be described in detail here.

[0100] It should be understood that, under the guidance of the present invention, ordinary technicians in this field can also make various changes such as substitutions and simple combinations without departing from the scope of protection of the claims of the present invention. The scope of protection of the rights of the present invention shall be based on the claims.

Claims

1. A friction nanogenerator with a multi-layer friction layer, the friction nanogenerator comprising electrodes, wires and connecting base springs, characterized in that: The electrode is divided into a top electrode and a bottom electrode, wherein the top electrode is composed of a positive friction layer and an upper substrate; the bottom electrode is composed of a negative friction layer with a multi-layer structure and a lower substrate; Wires, which are respectively led out from the top electrode and the bottom electrode; At least four connecting base springs, used to connect the upper base and the lower base; The positive friction layer is composed of a conductive film and is adhered to the upper substrate via a foam buffer layer; The negative friction layer with a multi-layer structure consists of a Mxene / melamine foam layer, a silicone rubber layer and a TiO2 nanotube array layer; the silicone rubber wraps the Mxene / melamine foam, adheres to the TiO2 nanotube array by self-adsorption, and is adhered to the lower substrate through the foam buffer layer.

2. The friction nanogenerator with a multi-layer friction layer according to claim 1, characterized in that: Preparation of the negative friction layer with a multi-layer structure: (a) hot pressing the melamine foam, using a hot pressing plate to hot press at 230-240° C. to obtain a hot pressed melamine foam; (b) drop-coating the Mxene aqueous solution onto the hot-pressed melamine foam to obtain a Mxene / melamine foam layer; (c) casting silicone rubber, mixing silicone rubber component A and component B in a volume ratio of 1:1, and casting the Mxene / melamine foam layer to obtain a Mxene / melamine foam / silicone rubber layer; (d) Fabrication of TiO2 nanotube arrays on Ti foil; (e) self-adhere the Mxene / melamine foam / silicone rubber layer onto the TiO2 nanotube array to obtain a Mxene / melamine foam / silicone rubber layer / TiO2 layer; The silicone rubber component A is a prepolymer; and component B is an adhesive.

3. A method for preparing a friction nanogenerator having a multi-layer friction layer according to claim 1, characterized in that: The positive friction layer is adhered to the upper substrate through the foam buffer layer as a top electrode; The negative friction layer with multilayer structure adheres to the TiO2 nanotube array as the bottom electrode by self-adsorption; Lead wires are led out from the top electrode and the bottom electrode respectively, and at least four connecting substrate springs are connected to the upper substrate and the lower substrate.

4. The method for preparing a friction nanogenerator having a multi-layer friction layer according to claim 3, characterized in that: Preparation of the negative friction layer with a multi-layer structure: (a) hot pressing the melamine foam, using a hot pressing plate to hot press at 230-240° C. to obtain a hot pressed melamine foam; (b) drop-coating the Mxene aqueous solution onto the hot-pressed melamine foam to obtain a Mxene / melamine foam layer; (c) casting silicone rubber, mixing silicone rubber component A and component B in a volume ratio of 1:1, and casting the Mxene / melamine foam layer to obtain a Mxene / melamine foam / silicone rubber layer; (d) Fabrication of TiO2 nanotube arrays on Ti foil; (e) self-adhere the Mxene / melamine foam / silicone rubber layer onto the TiO2 nanotube array to obtain a Mxene / melamine foam / silicone rubber layer / TiO2 layer; The silicone rubber component A is a prepolymer; and component B is an adhesive.

5. The method for preparing a friction nanogenerator having a multi-layer friction layer according to claim 4, characterized in that: The concentration of the Mxene aqueous solution is 5%wt~10%wt.

6. The method for preparing a friction nanogenerator having a multi-layer friction layer according to claim 4, characterized in that: The Mxene / melamine foam layer needs to be cured for more than 4 hours at room temperature after casting the silicone rubber to obtain the Mxene / melamine foam / silicone rubber layer.

7. An application of the friction nanogenerator with a multi-layer friction layer according to claim 1, characterized in that: Application of the friction nanogenerator in electrochemical cathodic protection.